UJI DIAGNOSTIK TORONTO CLINICAL SCORING SYSTEM TERHADAP DIAGNOSIS NEUROPATI PERIFER TERINDUKSI KEMOTERAPI - Aldy Novriansyah, Manfaluthy Hakim, Aru Wicaksono Sudoyo, Tiara Aninditha, Herqutanto (NEURONA, 2014)
INTRODUCTION CHEMOTHERAPYINDUCED PERIPHERAL NEUROPATHY CIPN IS AN ADVERSE EFFECT OF NEUROTOXIC CHEMOTHERAPY THAT DECREASE THE PATIENTS QUALITY OF LIFE AND OBSTRUCT THE PROVISION OF OPTIMAL CHEMOTHERAPY EARLY DETECTION IS NEEDED BY A SIMPLE SCREENING TOOL THATHAS A NEAR ACCURACY TO ELECTRONEUROGRAPHY ENG AS THE GOLD STANDARD FOR THE DIAGNOSIS OF NEUROPATHY THE TORONTO CLINICAL SCORING SYSTEM TCSS IS ANEASY AND SUPERIOR TOOL FOR DIABETIC NEUROPATHYSCREENING SIMILARITY BETWEEN DIABETIC NEUROPATHY AND CIPNS CLINICAL PICTURE COULD MAKE THE TCSS AS A SCREENING TOOL FOR CIPN